Numerical simulations of cross wind effects on cyclist aerodynamic resistance - Malizia, F.; Montazeri, H.; Hespel, P.; Blocken, B. (Journal of Science and Cycling, 2015)
Introduction: In outdoor cycling, cross wind can affect the race strategy and the final results. Ad-hoc strategies, like echelons and Belgian tourniquet formations, are indeed adopted by cyclists to reduce wind effects and aerodynamic drag. Forces and moments generated by cross winds have been often studied for isolated wheels [1,2] and for an entire isolated cyclist [3-5]. However, to the best of our knowledge, the impact of cross wind on a couple of cyclists has not yet been investigated. In this study, Computational Fluid Dynamics (CFD) simulations are used to evaluate the effect of cross wind on the aerodynamic resistance of a couple of cyclists in two different configurations: (1) when the trailing cyclist is placed in line with the leading cyclist (Fig. 1a) and (2) when both cyclists are staggered (Fig. 1b). To compare the results, additional simulations have been performed for a single cyclist. Moreover, the impact of the upstream turbulence intensity is investigated.